Pan My Religion Says 'Halfers'!: Top TT Pannist Tells of Work 'Up North' - Singh, Valentino (Sunday Guardian)
In this article well-known pannist, Annise "Halfers" Hadeed, from Trinidad and Tobago recounts his love of pan and his involvement in pan since childhood. Halfers moved to New York and Washington and travelled the length and breadth of Europe, playing at some of the most highly acclaimed music halls. Also, he expressed disappointment that pan was not yet on the school curriculum in Trinidad since there was evidence of opportunities for people to play pan professionally.
Keywords: Musicians -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago